Oxidation of norbornene over vanadium-substituted phosphomolybdic acid catalysts and spectroscopic investigations - Raj, N. K. K.; Ramaswamy, A.; Manikandan, Palanichamy (Journal of Molecular Catalysis A-Chemical, 2005)
Oxidation of norbornene has been carried out over mono-, di- and tri-vanadium-substituted phosphomolybdic acid catalysts with aqueous hydrogen peroxide (aq. H2O2) as an oxidant in different solvents. Monovanadium-substituted phosphomolybdic acid catalyst was found to be better than other catalysts for the above reaction and acetonitrile was the suitable solvent. At the optimum temperature of 60 degreesC, the norbornene conversion was 70% and the selectivity for 2,3-epoxy norbornane was 58%. The side products were norborneols and 2-norbornanone. The lower selectivity of 2,3-epoxy norbornane with aq. H2O2 is attributed to the simultaneous formation of other products, norborneols and 2-norbornanone. The norborneols are formed from norbornene by acid-catalyzed reaction. Other oxidants like urea-hydrogen peroxide adduct (UHP) and tert-butyl hydrogen peroxide (TBHP) were also tested for norbornene oxidation reaction. With UHP, the conversion was almost same (69%) as that of aq. H2O2 reaction; however, 2,3-epoxy norbornane was the main product with >97% selectivity. Thus, the overall yield was 66.9% at 60 degreesC after 4 h. The high selectivity with UHP is attributed to the controlled release of H2O2, absence of water and less acidic nature of UHP. With TBHP the selectivity for the epoxide was >96%; however, the conversion was low (27%). A mechanism for the norbornene oxidation is believed to be proceeding via V(5+)-peroxo and V(4+)-superoxo intermediates. NMR, EPR and UV-vis spectroscopic techniques were employed to understand the reaction intermediates and reaction pathways. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: 2; 3-epoxy norbornane; aq. H2O2; epoxidation; EPR; NMR; norbornene; urea-H2O2 adduct; UV-Vis; vanadium-substituted phosphomolybdic acid

Phase transfer of oleic acid capped NicoreAgshell nanoparticles assisted by the flexibility of oleic acid on the surface of silver - Bala, Tanushree; Swami, A.; Bhagavatula L. V. Prasad; Sastry, M. (Journal of Colloid and Interface Science, 2005)
The phase transfer protocols in vogue for the oleic acid capped silver nanoparticles, viz., salt-induced precipitation and redispersion or phosphoric acid-induced method, are examined and compared thoroughly. A comprehensive evaluation with respect to the mechanistic aspects involved is made and the merits and demerits of the different procedures are delineated. It is found that the salt-induced precipitation and redispersion is more versatile in that the precipitate can actually be redispersed in both aqueous and organic media. However, in terms of mechanism both the routes seem to be very similar wherein the orientational change of oleic acid on the silver surface in the two different environments-organic and aqueous-plays a crucial role in the adaptability of the system to the different environments. Subsequently, this change of orientation of oleic acid on silver surface in aqueous and organic media has been utilized to phase transfer Ni-based nanoparticulate systems. The nascent oleic acid-capped Ni nanoparticles, which were synthesized by a foam-based protocol, were dispersible in water but not in nonpolar organic media such as cyclohexane or toluene. Then, just by coating a thin shell of silver on them we could achieve complete phase transfer of the NicoreAgshell from aqueous to organic media following similar procedures used for oleic acid-capped silver nanoparticles. Here, the phase transfer seems to be facilitated by the orientational flexibility of oleic acid on the silver surface as opposed to other metal surfaces as evidenced from the infrared and thermogravimetric analyses of oleic acid-capped Ni and NicoreAgshell nanoparticles. This orientation-assisted phase transfer method could be generalized and can be adapted to other systems where, if the nascent nanoparticles cannot be phase transferred as is, they can be coated by a silver shell and oleic acid making them suitable for dispersion in both aqueous and organic media. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: (1) HNMR; FTIR; Phase transfer; transmetalation core-shell nanoparticles; UV-Vis

Synthesis and characterization of TAPO-31 molecular sieves using tripropylamine template - Venkatathri, N.; Shetty, V. N. (Catalysis Communications, 2006)
TAPO-31 was synthesized hydrothermally using a novel template tri-n-propylamine for the first time. C and N analysis shows the butanol from titanium tetrabutoxide plays an important role in the synthesis. The incorporation of titanium into framework of phosphorous and both aluminiurn and phosphorous sites was suggested from elemental analysis. Isomorphous substitution of titanium (III) in AlPO framework was confirmed from ESR and (31)p MASNMR spectra. UV-Vis and XPS spectra revealed a partial oxidation of framework titanium (III) into titanium (IV) in the calcined TAPO-31 and thus the presence of redox centers in the products. The higher titanium content (Al/Ti = 10) TAPO-31 sample shows higher activity for phenol hydroxylation compared to lower titanium content (Al/Ti = 20) and Titanium impregnated AIPO(4)-31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ESR; FT-IR; MASNMR; SEM; TAPO-31; TG/DTA; tripropylamine; UV-Vis; XPS; XRD

Synthesis, characterization and catalytic properties of vanadium aluminophosphate molecular sieves VAPO-31 and VAPSO-Amr from non-aqueous media - Venkatathri, N. (Applied Catalysis A-General, 2006)
Vanadium samples containing aluminophosphate molecular sieve (VAPO-31) and amorphous vanadium silicoaluminophosphate (VAPSO-Amr) have been synthesized using hexamethyleneimine template from non-aqueous media for the first time. XRD and SEM analyses confirm the phase purity of the synthesized samples. FT-IR analysis suggests the incorporation of V4+ in the aluminophosphate framework. ESR, UV-vis spectroscopic, and XPS techniques and cyclicvoltametric studies confirm the incorporation of vanadium and reveal its presence in tetrahedral and square pyramidal environments in the as-synthesized samples. Cyclic voltammetry reveals the presence of two redox couples in VAPO-31. This catalyst is found to be a good oxidation catalyst. Although most of the properties of VAPO-31NA and VAPSO-Amr are similar, the latter can access more vanadium and V4+ ions. Compared to aqueous media samples, it can incorporate more vanadium especially V5+, ions and has been found to be better oxidation catalyst. The physicochemical properties also change with media. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cyclic voltammetry; ESR; FT-IR; MAS NMR; non-aqueous; SEM; TG/DTA; UV-Vis; VAPO-31; XPS; XRD